Evaluation of teacher performance in post-certification classroom action research at the vocational school - Dwi Elvina; Wakhinuddin Wakhinuddin; Edidas Edidas; Ambiyar Ambiyar (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2022)
The purpose of this study was to assess teacher performance in classroom action research at SMK N 2 Sungai Penuh after certification using the goal free evaluation model. Teacher performance in classroom action research aims to improve the quality of Indonesian education, one of which is through educator-certified teachers who have professional competence by conducting classroom action research. Evaluation of attachment to the positive, negative, and side (neutral) impacts of the post-certification program. The research subjects were teachers who were certified educators and taught for about ten years, totaling 56 people. He research method is qualitative. Data collection techniques using questionnaires, interviews, documentation and observation. The results of the research show that the certification program in improving the welfare of economic teachers has been successful but not in improving teacher performance in classroom action research. The negative impacts that arise must be considered and corrected so as not to disrupt the stability of an already good program.